Intruder detection in camera networks using the one-class neighbor machine - Ahmed, Tarem Ozair; Wei, Xianglin; Ahmed, Supriyo; Pathan, Al-Sakib Khan (2011)
We propose a new algorithm based on machine learning techniques for automatic intruder detection in surveillance networks. The algorithm is theoretically founded on the concept of minimum volume sets. Through application to real images from an example, simple closed-circuit television system and comparison with some existing algorithms, we show that it is possible to easily obtain high detection accuracy with low false alarm rates.